Perancangan Sistem Informasi Penjualan Berbasis Website pada PT. Reftech Jaya Optima - Ahmad Rifqi Baihaqi; Perwito; Cahyadi Agustin (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
PT Reftech Jaya Optima is a trading company in the field of air compressors, HVAC, fire fighting systems, mechanical and electrical contractors. PT Reftech Jaya Optima has many cash sales and credit sales transactions. Recording these sales takes place using a spreadsheet, so it is still inefficient in presenting sales reports. In order to solve the problems that occur, a website-based sales information system is needed. The author builds a system design using PHPRad software, PHP programming language and MySQL as a database. Descriptive qualitative approach is used to collect data in this research. While the system development method used in this research is the waterfall model. System design is done using the Unified Modeling Language (UML). With this, users will find it easier to complete the sales recording process with the help of a website-based sales information system.